Two forms of transcription factor TFIIIC in extracts from HeLa cells. - Van Dyke, M W (1987)
Partially-purified preparations of transcription factor TFIIIC derived from either cytoplasmic (S100) or nuclear (NE) HeLa cell extracts possessed comparable activities when assayed by in vitro transcription, although it was possible to detect sequence-specific binding to the VAI RNA gene promoter by DNase I footprinting only with TFIIIC (NE). On the basis of mixing experiments, this difference could not be ascribed to either transcriptional or DNA-binding inhibitors. These findings provide further evidence for the existence of two forms of TFIIIC: one which is present in both extracts and is transcriptionally active; another which predominates in nuclear extracts and is transcriptionally inactive.